Pengembangan Karir pada PT. Karya Sukses Maju Bersama Medan - Brandon Yapto; Muhammad Agung Anggoro; Nurul Wardani Lubis (IPM2KPE, 2023)
This research aims to determine and test the influence of training, position promotion and competency on career development at PT Karya Sukses Maju Bersama Medan. The research method is a descriptive method through surveys. The results of the research show that training has an influence on career development at PT Karya Sukses Maju Bersama Medan with a value of tcount>ttable (2.280>1.994) and sig. of 0.026 (0.026<0.05). Position Promotion has an effect on Career Development at PT Karya Sukses Maju Bersama Medan with a value of tcount> ttable (5.266>1.994) and sig. of 0.000 (0.000<0.05). Competence influences career development at PT Karya Sukses Maju Bersama Medan with a value of tcount>ttable (7.176>1.994) and sig.of 0.000 (0.000<0.05). Training, Position Promotion and Competency influences Career Development at PT Karya Sukses Maju Bersama Medan with a value of Fcount> Ftable (76.452>2.74) andsig. 0.000<0.05. Career development was explained by independent variables by 75.9%, but the remaining 24.1% was explained by other variables not studied, such as transfers, education and work experience. Conclusion, Training influences career development at PT Karya Sukses Maju Bersama Medan. Position promotions influence career development at PT Karya Sukses Maju Bersama Medan. Competency influences career development at PT Karya Sukses Maju Bersama Medan. Training, Position Promotion and Competency influence Career Development at PT Karya Sukses Maju Bersama Medan. Keywords: Position Promotion, Competency, Training